SUCCESSFUL PERFORMANCE APPRAISAL IN A SCHOOL ORGANISATION - SHONHIWA, DOCTOR CAXTON (IJRDO- Journal of Educational Research, 2017)
The present paper discusses the importance of performance appraisal using the school as the site of implementation. Schools, just like any other public or private organization, have many employees or staff members whose performance has to be periodically appraised for their individual growth and that of their organisation. The paper argues that performance appraisal should be viewed as a process, and not simply as the creation of ubiquitous standards. The overriding purpose of performance appraisal is to help staff to improve and, thus, to improve organisational effectiveness. Performance appraisal therefore addresses institutional needs as well as staff member needs, abilities, motivation and expectancies. Effective appraisal systems must possess the attributes of clarity, openness, and fairness. Appraisal activities, as an ongoing process should connect the process to organisational functioning and have as their focus staff improvement, not simply salary adjustment and or disciplinary action. Appraisal systems are related to institutional productivity requirements. They are expected to reveal under- productive units and to serve as a response to focus attention on problem areas and also reward productive units and staff.